POSTCOLONIAL THEORY: LACK FACTORS OF L2 ON L1 IN THE WRITING SKILL OR VICE VERSA - Prasetyo, Dodi Erwin (ETERNAL (English, Teaching, Learning, and Research Journal), 2021)
the spread of English affects either in the education field or other language use. This emerges postcolonial theory which stresses on how the second language affects to first language or vice versa. this paper aims at discussing what postcolonial theory is, explaining the urgency of postcolonial theory for Egnlish writing, reviewing L1 and L2 written acquisitions and pondering some lack factors of L2 on L1 in the writing skill or vice versa. The factors were categorized as internal and external factors. Internal factors delineate as students-self ability in terms of psychological factors, socio cultural factors and linguistic factors. Meanwhile, external factors derive as students’ environments effects in terms of family factors, peer factors and instructor or teacher factors. The suggestion offers to the pedagogical aspects.